2014
DOI: 10.4103/1305-7456.126240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporation of silane in the bonding agent on the repair potential of machinable esthetic blocks

Abstract: Objective:To investigate the repair potential of CAD/CAM (computer-aided design/computer-aided manufacturing) ceramic and composite blocks using a silane-containing bonding agent with different repair protocols.Materials and Methods:Twenty-four discs were constructed from CAD/CAM ceramic and composite blocks. The discs were divided into six groups according to surface pre-treatment employed; GI: Diamond stone roughening (SR), GII: SR+ silanization (SR+S), GIII: Hydrofluoric acid etching (HF), GIV: HF+ silaniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
63
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 29 publications
7
63
0
7
Order By: Relevance
“…Another explanation is that the concentration of silane in MUA might not be sufficient to react with the hydroxyl groups of the ceramic surface. This was confirmed by the studies by Zaghloul et al35 and Kalavacharla et al26 According to these authors, treatment with silane followed by MUA significantly improved the bond strength between the ceramic and the composite resin. The additional silanization step enhanced chemical bonding to the exposed hydroxyl groups and surface wettability with resin impregnation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Another explanation is that the concentration of silane in MUA might not be sufficient to react with the hydroxyl groups of the ceramic surface. This was confirmed by the studies by Zaghloul et al35 and Kalavacharla et al26 According to these authors, treatment with silane followed by MUA significantly improved the bond strength between the ceramic and the composite resin. The additional silanization step enhanced chemical bonding to the exposed hydroxyl groups and surface wettability with resin impregnation.…”
Section: Discussionsupporting
confidence: 60%
“…Because the pH of MUAs is 2.2 to 3.2 for self-etching capability, a self-condensation reaction occurs in the silanol groups of hydrolyzed silane 3334. A second possible explanation is that Bis-GMA in MUAs significantly inhibits the condensation reaction between the hydroxyl groups of lithium disilicate ceramic and the silanol groups of silane 35. Moreover, extra resin could inhibit the condensation reaction that releases water molecules according to the Le Chatelier principle 36.…”
Section: Discussionmentioning
confidence: 99%
“…The BisGMA component can prevent the reaction between the silane and the hydroxyl group of the ceramic surface containing silica . A balance between the hydroxyl groups of the inorganic substrate and the hydrolysable functional groups in the silane is required to improve the bond strength . The results of the present study suggest that the silane rate in the universal adhesive (approximately 10% of the volume) is not sufficient to provide similar bond strength to the use of the silane separately, probably due to the incompatibility with the amount of hydroxyl groups in the inorganic phase of PICN.…”
Section: Discussionmentioning
confidence: 75%
“…The present study found the highest bond strength values for the groups treated with the silane, alone or combined to the silane‐containing adhesive, compared to the single use of silane‐containing adhesive (universal), accepting the first hypothesis. Universal adhesives were introduced to simplify the bonding protocol and, consequently, reduce the clinical time . Besides the silane already mentioned, the universal adhesive tested contains several components according to the manufacturer: MDP, BisGMA, Vitrebond Copolymer, HEMA, filler, ethanol water, and initiators.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, after heat-treating the silane, higher bond strength values may be achieved due to the removal of the upper layers of silane, leaving a more stable silane layer at the bonding interface 37 . Failure mode analysis showed that, in the three groups, mixed failure was predominant, indicating that there was a good interaction of the resin cement with the post and root dentin after the different surface treatments; thus, the adhesion process was effective 31,[39][40][41][42] . Previous studies have reported that clinically…”
Section: Discussionmentioning
confidence: 99%